Origins of post-COVID-19 inflation in Central European countries - Tomáš Šestořád; Natálie Dvořáková (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This paper examines the drivers of the post-pandemic surge in inflation in four small open economies: Czechia, Hungary, Poland, and Slovakia. For this purpose, a Bayesian structural vector autoregressive model with sign-zero restrictions and block exogeneity is employed. The results show that both foreign demand and foreign supply shocks have contributed significantly to inflation in the post-2020 period across countries, alongside notable contributions from domestic factors explaining differences among economies. Specifically, supply-side shocks are identified as the primary domestic factor across all countries, whereas domestic demand shocks were much less influential. Exchange rate shocks were pronounced in Hungary only, while monetary policy shocks have had a minimal impact on inflation since 2022 in all the countries considered. Additionally, we provide decompositions of core inflation, highlighting the predominance of domestic factors.
Keywords: C32; E31; E32; E52; F41; 330; Bayesian VAR; extraordinary events; inflation; sign-zero restrictions; small open economies